2013
DOI: 10.1590/s1519-99402013000300016
|View full text |Cite
|
Sign up to set email alerts
|

Respostas fisiológicas e produtivas de vacas holandesas em lactação submetidas ou não a sombreamento e aspersão na pré-ordenha

Abstract: Objetivou-se, avaliar a influência de alguns recursos de climatização na produção e composição do leite e nas variáveis fisiológicas, freqüência respiratória, freqüência cardíaca, temperatura retal. Foram utilizadas 14 vacas da raça Holandesa, em um experimento com delineamento inteiramente casualizado com dois tratamentos: sala de espera com sombreamento acrescido de aspersão (climatizado) e sala de espera sem estrutura de climatização (não climatizado), sendo sete vacas por tratamento. Os dados climáticos de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 15 publications
2
7
0
9
Order By: Relevance
“…S+S and S+S+V had average values of rectal temperature of 38.52 and 38.50 °C, respectively, representing an average reduction of 0.9 °C in rectal temperature when compared to EXT. Similar results were obtained by CERUTTI et al (2013), who reported a reduction of 0.6 °C in rectal temperature of cows submitted to climatization in pre-milking (shading and sprinkling) when compared to treatment without acclimatization.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…S+S and S+S+V had average values of rectal temperature of 38.52 and 38.50 °C, respectively, representing an average reduction of 0.9 °C in rectal temperature when compared to EXT. Similar results were obtained by CERUTTI et al (2013), who reported a reduction of 0.6 °C in rectal temperature of cows submitted to climatization in pre-milking (shading and sprinkling) when compared to treatment without acclimatization.…”
Section: Resultssupporting
confidence: 87%
“…Among the climatization techniques, shading has an important role in reducing the radiant heat load on animals . Water sprinkling is also an important technique that aims to speed up heat exchange by the evaporation process (SCHÜTZ et al, 2011;CERUTTI et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Cerutti et al (2013), assessing the productive response of Dutch-breed animals to the sprinkling system in holding pen found a growth of 12.4% for the animals subjected to this system. Tresoldi, Schütz and Tucker (2016),working with Dutch cows and different cooling times, using high-flow sprinklers (0, 0.5, 1.5, 3 and 13 min., flow of 4.9 L min -1 ), verified cooling benefits, as well as changes in air temperature, more pronounced when water was sprinkled for longer (over 13 min.…”
Section: Resultsmentioning
confidence: 96%
“…Almeida, Pandorfi, Guiselini, Almeida and Morril (2010), in their turn, found an increase of 4.35% in the milk production of cows subjected to climatization with a similar system. Nevertheless, to analyze the viability of a climatization system, the productive response alone is insufficient, because the adoption of costly measures to mitigate the effects of thermal stress can make its use unfeasible, especially when the number of animals in production is not enough to dilute, in the short term, the fixed costs of the technology adopted, and productivity gains are not sufficiently high to offset the investment (Cerutti, Bermudes, Viegas, & Martins, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A maior CTR registrada nos horários mais quentes deve-se a maior incidência da radiação solar nestes horários. (CERUTTI et al, 2013).…”
Section: Resultsunclassified